2013
DOI: 10.1136/bcr-2013-010133
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic malignant syndrome associated with haloperidol use in critical care setting: should haloperidol still be considered the drug of choice for the management of delirium in the critical care setting?

Abstract: A 48-year-old man was brought to the emergency department because of intoxication. The patient was in respiratory distress, subsequently intubated for airway protection. On hospital day 5, he was diagnosed with delirium. Haloperidol was initiated at 5 mg intravenous every 6 h and titrated up to a dose of 60 mg /day over 5 days. On hospital day 18, his temperature peaked to 107.1°F. Other symptoms included mental status change, muscular rigidity and autonomic dysfunction. Neuroleptic malignant syndrome (NMS) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These acute conditions are routinely managed with antipsychotic drugs such as short-acting injections of haloperidol and olanzapine [28]. NMS following exposure to antipsychotics in emergency, critical care, and trauma care settings has been reported [29][30][31][32]. Consistently, the result of the univariate analysis in our study indicated that presentation with acute conditions was a possible risk factor for NMS.…”
Section: Risk Of Neuroleptic Malignant Syndromesupporting
confidence: 85%
“…These acute conditions are routinely managed with antipsychotic drugs such as short-acting injections of haloperidol and olanzapine [28]. NMS following exposure to antipsychotics in emergency, critical care, and trauma care settings has been reported [29][30][31][32]. Consistently, the result of the univariate analysis in our study indicated that presentation with acute conditions was a possible risk factor for NMS.…”
Section: Risk Of Neuroleptic Malignant Syndromesupporting
confidence: 85%
“…Psychostimulant intoxication, neuroleptic malignant syndrome and serotonin syndrome were reported to be clinically overlapping (Demirkiran et al, 1996). Dantrolene has been used successfully in the treatment of both methamphetamine toxicity and neuroleptic malignant syndrome (Dixit et al, 2013). Indeed, we have seen a decrease in myoglobin levels shortly after administration of dantrolene.…”
Section: )mentioning
confidence: 77%
“…Initial symptoms in NMS are mental status changes, followed by muscular rigidity, fever, and finally dysautonomia in 70% of cases [ 3 ]. The onset of NMS symptoms from antipsychotic exposure is variable, with 16% of cases occurring within 24 hours, 66% of cases within seven days, and nearly all cases within 30 days [ 4 ]. Because several other syndromes can result in similar symptoms, brain imaging, lumbar puncture (LP), and electroencephalogram (EEG) should be obtained to exclude organic causes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%